Pretreatment MicroRNA Level and Outcome in Sorafenib-treated Hepatocellular Carcinoma. (August 2014) - Gyöngyösi, Benedek; Végh, Éva; Járay, Balázs; Székely, Eszter; Fassan, Matteo; Bodoky, György; Schaff, Zsuzsa; Kiss, András
Sorafenib represents the first effective targeted therapy for advanced stage hepatocellular carcinoma (HCC); however, adequate patient stratification regarding sorafenib-responsiveness is still missing. Our aim was to analyse the association between the pretreatment microRNA profile of HCC and patient survival under sorafenib treatment. Total RNA was extracted from diagnostic fine-needle aspiration biopsy (FNAB) cytological smears of 20 advanced stage HCC patients collected between June 2008 and July 2012. All patients underwent sorafenib administration after FNA. Clinicopathological and survival data were recorded. Fourteen frequently deregulated miRNAs in HCC (miR-17-5p, miR-18a, miR-21, miR-34a, miR-122, miR-195, miR-210, miR-214, miR-221, miR-222, miR-223, miR-224, miR-140, miR-328) were tested by qRT-PCR. NormFinder software was used to select proper miR (mir-140) as a reference. Satisfactory amount of total RNA was obtained from all the considered samples (mean 10.8 ± 9.3 µg, range 0.2–32.2 µg). Among the analysed miRNAs, high miR-214 expression was associated with smaller tumor size ( p =0.019), whereas high miR-17-5p expression correlated with better Eastern Cooperative Oncology Group performance status ( p =0.003). The survival analysis revealed that high miR-224 expression was associated with increased progression-free and overall survival (PFS p =0.029; OS p =0.012). Pretreatment microRNA profiling, especially miR-224 expression, might serve as an ancillary tool for the better assessment of expected survival rates for patients under sorafenib treatment.